Optimization and Benefit Assessment of LID Layout Based on the MCDA Approach at a Campus Scale - Zexin Lei; Lijun Li; Yanrou Wei; Wenzheng Zhang; Junjie Luo; Xuqiang Zhao (Land)
Low-impact development (LID) offers environmental, economic, and social benefits, yet research on optimizing facility combinations remains limited. This study evaluates four representative LID types—green roofs, sunken green spaces, permeable pavement, and rain gardens—using an integrated framework combining the Storm Water Management Model (SWMM), NSGA-II genetic algorithm, and Analytic Hierarchy Process (AHP) at Taiyuan University of Technology in Shanxi Province, China. Based on site constraints, each LID type was pre-assigned to suitable subareas, and optimization focused on determining proportional allocations within these areas. SWMM simulations revealed that permeable paving achieved the highest runoff reduction (up to 19.4% at 65% coverage) and strong cost-effectiveness (0.013 USD per % reduction). NSGA-II was used to generate a set of optimal solutions by minimizing construction costs and maximizing runoff and pollutant reductions. AHP then ranked these solutions according to their environmental, economic, and social benefits. In this case, the ideal mix—subject to site-specific constraints and model assumptions—includes 28.58% green roofs, 19.37% sunken green spaces, 48.68% permeable paving, and 3.37% rain gardens. The study proposes a sponge campus renewal strategy, offering theoretical and practical insights for sustainable urban development and precise environmental management.